Models of the classifier of prerequisites for the occurrence of road accidents to predict dangerous situations at intersections - Byzkrovnyi, Oleksandr; Smelyakov, Kyrylo (INNOVATIVE TECHNOLOGIES AND SCIENTIFIC SOLUTIONS FOR INDUSTRIES, 2025)
The subject matter: this study focuses on the preconditions for the occurrence of road traffic accidents at intersections and areas with limited visibility; the use of computer vision models for classifying the preconditions of road traffic accidents and evaluating the effectiveness of their use in real-time operation. The goal of the study is to compare computer vision models for the task of classifying the preconditions of traffic accidents for real-time operation. The study involves comparing models using the Jetson TX2 platform and determining the effectiveness of this approach for generating real-time warning signals for drivers. Tasks: explore computer vision models such as Detectron2 and YOLOv7 for the task of classifying traffic accident preconditions in terms of model performance, ease of dataset creation, model training, and deployment. Compare YOLOv8 and DetectNet_v2 on a single-board computer Jetson TX2 in terms of processing speed. The methods used include training and using machine learning models, as well as simulating hazardous situations using software such as BeamNG.tech and CARLA. A comparative analysis of the application results of the models was conducted using performance evaluation metrics. The main results of the study include identifying the most effective model for classification tasks on the Jetson TX2 single-board computer – DetectNet_v2; a positive evaluation of the effectiveness of this approach for real-time driver warning, although certain limitations were noted regarding the size of the training dataset and the complexity of its preparation. Conclusions. The following computer vision algorithms were examined: Detectron2, YOLOv7, and DetectNet_v2. It was found that YOLOv7 outperforms Detectron2 in detecting the preconditions of traffic accidents in images. However, DetectNet_v2 was found to be better suited for deployment on the Jetson TX2 single-board computer compared to YOLOv7. Additionally, based on experimental findings, it was concluded that the application of this approach to predicting accident preconditions is problematic due to difficulties in creating a training dataset – specifically, the variability of precondition scenarios.